Electroreforming of Biomass for Value-Added Products - Zi Iun Lai (MDPI AG, 2021)
Humanity’s overreliance on fossil fuels for chemical and energy production has resulted in uncontrollable carbon emissions that have warranted widespread concern regarding global warming. To address this issue, there is a growing body of research on renewable resources such as biomass, of which cellulose is the most abundant type. In particular, the electrochemical reforming of biomass is especially promising, as it allows greater control over valorization processes and requires milder conditions. Driven by renewable electricity, electroreforming of biomass can be green and sustainable. Moreover, green hydrogen generation can be coupled to anodic biomass electroforming, which has attracted ever-increasing attention. The following review is a summary of recent developments related to electroreforming cellulose and its derivatives (glucose, hydroxymethylfurfural, levulinic acid). The electroreforming of biomass can be achieved on the anode of an electrochemical cell through electrooxidation, as well as on the cathode through electroreduction. Recent advances in the anodic electroreforming of cellulose and cellulose-derived glucose and 5-hydrooxylmethoylfurural (5-HMF) are first summarized. Then, the key achievements in the cathodic electroreforming of cellulose and cellulose-derived 5-HMF and levulinic acid are discussed. Afterward, the emerging research focusing on coupling hydrogen evolution with anodic biomass reforming for the cogeneration of green hydrogen fuel and value-added chemicals is reviewed. The final chapter of this paper provides our perspective on the challenges and future research directions of biomass electroreforming.